Bamboo fiber improves piglet growth performance by regulating the microbial composition of lactating sows and their offspring piglets - Dai, Fawen; Lin, Tao; Jin, Muqu; Huang, Xia; Wang, Lu; Ma, Jing; Yu, Hang; Fan, Xianlin; Nong, Xiang; Zuo, Jianjun (Frontiers in Microbiology, 2024)
Introduction Feeding bamboo powder is a kind of fiber raw material mainly composed of insoluble dietary fiber (IDF). In this study, IDF-based rice husk meal and feeding bamboo powder were used to compare the effects of bamboo fiber on fecal microflora and the performance of lactating sows and their offspring piglets. Methods Thirty healthy crossbred gilts (Yorkshire × Landrace) at day 105 of gestation were randomly allocated into three groups: CON, TRE1 supplemented with 2% BBF1 (feeding bamboo powder), and TRE2 supplemented with 2% BBF2 (99% feeding bamboo powder +1% bamboo fiber polymer material). The reproductive performance, serum indexes, and fecal microbiota of sows and piglets were analyzed. The results showed that, compared with CON, the average feed intake of sows in TRE1 during the second week of lactation was significantly increased by 21.96% (p < 0.05), the average daily gain (ADG) per litter in TRE1 on 11–21 days and 3–21 days of lactation was significantly increased by 50.68 and 31.61%, respectively (p < 0.05), and the serum triglyceride content of sows in TRE1 on the 21st day of lactation was significantly increased (p < 0.05). The 16S rRNA analysis showed that dietary bamboo fiber significantly increased the fecal microbial richness index Ace, Chao, and Sobs of sows (p < 0.05) and tended to increase the Sobs index of suckling piglets on day 21 (p < 0.10). Compared with CON, BBF1 supplementation significantly decreased the abundance of Christensenellaceae_R-7_group in feces of sows on days 7 and 21 after delivery (p < 0.05), while BBF2 decreased the genera Christensenellaceae_R-7_group on days 7 (p < 0.10) and 21 (p < 0.05) after delivery. Spearman correlation analysis showed that the abundance of Phascolarctobacterium in the feces of piglets on the 21st day after delivery was significantly positively correlated with diarrhea rate and significantly negatively correlated with ADG per litter, day 21 litter weight, and 3- to 21-day survival rate. In contrast, Christensenellaceae_R-7_group was significantly negatively correlated with diarrhea rate and positively correlated with ADG per litter. Discussion These results indicated that maternal BBF1 supplementation improved the litter weight gain of suckling piglets, which was associated with the improvement of diversity and structure of the fecal microbiota in the piglets.